2015
DOI: 10.1016/j.meegid.2015.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-locus variable-number tandem repeat analysis of Leptospira interrogans and Leptospira borgpetersenii isolated from small feral and wild mammals in East Asia

Abstract: Leptospira spp. are the causative agents of a worldwide zoonosis, leptospirosis, maintained by various mammals. Each Leptospira serovar is frequently associated with a particular maintenance host, and recently, Leptospira genotype-host association has also been suggested to limit serovars to restricted areas. We investigated the molecular characteristics of L. interrogans and L. borgpetersenii which were isolated from small feral and wild animals in four East Asian states using multiple-locus variable-number t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…Although the majority of our samples came from water buffalo and the molecular analysis was limited, our findings may further support the previous reports regarding the diversification of Leptospira species [8, 17, 34], wherein this phenomenon can be attributed to maintenance of host animals (alteration of physiology or immune system) or environmental factors [14, 17]. L. borgpetersenii is known to have a broad host range [2, 17] and is restricted to animal-to-animal transmission [5], and therefore is more prone to diversification. A wider study coverage area along with the use of recent molecular typing methods, such as multiple-locus variable-number of tandem repeat analysis and multilocus sequence typing, should be employed in future studies to reveal the genetic diversity of Leptospira present in large ruminants in the Philippines.…”
Section: Discussionsupporting
confidence: 90%
“…Although the majority of our samples came from water buffalo and the molecular analysis was limited, our findings may further support the previous reports regarding the diversification of Leptospira species [8, 17, 34], wherein this phenomenon can be attributed to maintenance of host animals (alteration of physiology or immune system) or environmental factors [14, 17]. L. borgpetersenii is known to have a broad host range [2, 17] and is restricted to animal-to-animal transmission [5], and therefore is more prone to diversification. A wider study coverage area along with the use of recent molecular typing methods, such as multiple-locus variable-number of tandem repeat analysis and multilocus sequence typing, should be employed in future studies to reveal the genetic diversity of Leptospira present in large ruminants in the Philippines.…”
Section: Discussionsupporting
confidence: 90%
“…; Koizumi et al . ). A particularly interesting and deserves to be highlighted is that the high number of undescribed and unique VNTR patterns, both on L. interrogans / L. kirschneri (5/6, 83·3%) and on L. santarosai strains (17/17, 100%).…”
Section: Resultsmentioning
confidence: 97%
“…; Koizumi et al . ), highlighting the potential role of infected dogs as sources of infection for other susceptible hosts because they constantly shed leptospires in their urine. Recently, our group demonstrated that barely 20% of asymptomatic dogs may shed leptospires, mainly Icterohaemorrhagiae (Sant'anna et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathogenic serovars of L. interrogans serovar Icterohaemorrhagiae (strain WFA135), an isolate from Rattus norvegicus in Tokyo, Japan, serovar Manilae (strain UP-MMC-NIID) 31,32 and a saprophytic L. biflexa serovar Patoc (strain Patoc I) were used in this study. The serovar of WFA135 was determined by multiple loci variable number of tandem repeats analysis (MLVA) and DNA sequencing of the lic12008 gene 32,33 . Bacteria were cultured in enriched Ellinghausen-McCullough-Johnson-Harris (EMJH) liquid medium (BD Difco, NJ, USA) containing 25 μg/mL spectinomycin at 30 °C for 2 ( L. biflexa ) or 4 ( L. interrogans ) days until the stationary phase.…”
Section: Methodsmentioning
confidence: 99%